THE TRACES OF ISLAMIC CULTURAL HISTORY: ANALYZING THE CULTURAL VALUES THAT INSPIRE INDONESIAN MUSLIMS - Abdul Wahab Syakhrani; Agus Fawait; Zainol Hasan; Antono Damayanto (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2024)
The article "The Traces of Islamic Cultural History: Analyzing the Cultural Values that Inspire Indonesian Muslims" is an article that seeks to provide insight into the cultural values that inspire Indonesian Muslims and how these values are rooted in the history of Islam in Indonesia. It discusses the role of Islamic scholars, religious institutions, and cultural practices in shaping the development of Islamic values in Indonesia. It explores how local cultural traditions and practices have influenced the expression of Islam in Indonesia. The article argues that the cultural values that inspire Indonesian Muslims are shaped by the history of Islam in the region and by the interaction between Islamic traditions and local cultural practices. It also highlights the importance of studying the cultural values that inspire Indonesian Muslims better to understand the relationship between Islam and Indonesian culture. Overall, the article is a valuable contribution to studying Islamic culture in Indonesia, providing a detailed analysis of the cultural values that inspire Indonesian Muslims, and sheds light on the unique features of Indonesian Islam.